Marx about the social progress and fears of a frightened society: Marx’s opinion - Smirnov, Victor E. (Journal of the Belarusian State University. Sociology, 2019)
It is argued that the main contribution of Marx is the theoretical basis of the theory of social progress is relevant today more than ever. This statement is substantiated by objectively occurring social processes and by the absence of a new theory, that can adequately explain the essence of social development. Modern theories of classless society, sustainable development and the end of history as ways of ideological justification of the current social order satisfying the ruling class are criticized. The reasons of social fears to radical changes in society, which have arisen in the majority of the population of post-soviet countries over the past three decades are explained. The modern Marxʼs interpretation of the theory of social progress is offered on the basis of the analysis of historical events of the last decades.